Happy marriage?! Vol. 10 - Enjoji, Maki (Shojo beat manga., 2015)
"Chiwa Takanashi has married a total stranger- company president Hokuto Mamiya- to get her father out of debt. Chiwa has received a letter written to her by Hokuto's father revealing a secret she can't tell her husband. But when that secret is revealed to the entire Mamiya clan, it could ruin Chiwa and Hokuto's marriage..."